Penyuluhan dan Pelatihan Pengembangan Keterampilan Berpikir Kritis Melalui Metode Game dan Peta dalam Pembelajaran IPS di Masyarakat - Mutaqin, Alim; Wabiser, Yan Dirk; Marten Inggamer, Mamberuman; Engel Mawara, Ricky (J-Abdimas Cenderawasih, 2025)
This community service activity aims to improve students' critical thinking skills in learning Social Sciences (IPS) through training for teachers on the use of map-based educational game methods. The activity was carried out at SD Negeri 01 Pengabean, Losari District, Brebes Regency, involving 10 teachers as participants. The implementation method includes training, mentoring, and implementation in the classroom. The results of the activity showed an increase in teachers' abilities in designing critical thinking-based learning and a significant increase in student involvement. This approach has proven effective in creating a more active and meaningful learning atmosphere. This activity is expected to be replicated in other schools as an alternative contextual and innovative IPS learning strategy.